The University Library: Analysis and Proposals - Weinberg, Charles B. (Management Science, 1974)
The operation of the university library as a means to supply information is examined. It is shown that despite the increase in size of libraries, their standard of service is declining. Reasons for this decline are advanced. The strategic goals of the library are redefined with implications for the library's acquisition, shelving, and retention policies. A Bayesian approach is then developed for determining the information value of the library's resources. In contrast to other work in this field, stress is placed on user evaluation of the library's resources. The approach developed is applicable to decisions relating both to the acquisition of volumes and the maintenance of collections.